ISOLATION AND IDENTIFICATION OF BACTERIA CAUSING SECONDARY WOUND INFECTIONS IN DIABETES MELLITUS PATIENTS IN JAMBI CITY - Qatrinnada Maulidya Akmal; Hanina; Humaryanto; Lipinwati; Rita Halim (Fakultas Kedokteran Universitas Sriwijaya, 2024)
The isolation and identification of secondary wound infection bacteria in diabetic patients in Jambi City are crucial for developing effective treatment strategies. The diversity of infecting bacteria underscores the importance of discerning the most prevalent types. This research aims to identify bacteria causing secondary wound infections in diabetic patients. Researchers obtained samples for this descriptive cross-sectional study by swabbing the incisions of diabetic patients at RSUD H. Abdul Manap in Jambi City between August and October 2023. Gram staining, culturing, and enzymatic tests were performed on the samples. Out of 21 samples, the age group most affected was 45-59 years (61.9%), predominantly male (81%), engaged in high-risk occupations (42.9%), with lower extremity wounds (90.5%), and primary wounds diagnosed as vulnus scissum and vulnus abrasio (33.3%). In contrast, DM ulcers constituted 66.7% of secondary wound infections in diabetic patients. Bacterial identification revealed Staphylococcus aureus as the predominant species (42.9%) responsible for secondary wound infections in diabetic patients. This study underscores the dominance of Staphylococcus aureus in secondary wound infections among diabetic patients.